PENERAPAN METODE BENT LAMINATION PADA PROSES PELENGKUNGAN KOMPONEN KURSI - Wijayanto, Arip; Mulyana, Elda (Tengkawang : Jurnal Ilmu Kehutanan, 2024)
Currently, furniture products use wooden components in a curved shape to highlight their aesthetic value. However, the components in the curved form are still mostly done in the conventional way. The aim of this study is to apply the bent lamination method to the components of the back legs and the backrest of the chair product. The stages of work started with making a chair design that has a curved shape on the back legs and backrest. Next was the preparation of laminate from teak wood with a thickness of 3 mm each as many as 14 for the back legs and 10 for the backrest. The lamination process was carried out with a polyurethane adhesive and pressing for 3 hours on a bending mal. After the bending process, observations of changes in the shape of each component were carried out. The application of the bent lamination method produces a curved back legs component with a radius of 100 mm, 250 mm, and 290 mm, a thickness of 40 mm and a width of 30 mm, and a curved backrest component with a radius of 205 mm, a thickness of 30 mm and a width of 40 mm. The results of observations of changes in shape were not found after the bending process.Keywords: bent lamination, chair, furniture, teakAbstrakSaat ini banyak produk furnitur menggunakan komponen kayu dalam bentuk lengkung untuk menonjolkan nilai estetikanya. Namun hingga saat ini komponen dalam bentuk lengkung tersebut masih banyak dilakukan dengan cara konvensional. Tujuan dari penelitian ini yaitu untuk menerapkan metode bent lamination pada komponen kaki belakang dan sandaran punggung produk kursi. Tahapan pengerjaan dimulai dari pembuatan desain kursi yang memiliki bentuk lengkung pada kaki belakang dan sandaran punggung. Selanjutnya yaitu penyiapan lamina dari kayu jati dengan tebal 3 mm masing-masing sebanyak 14 untuk komponen kaki belakang dan 10 untuk sandaran punggung. Proses laminasi dilakukan dengan perekat jenis poliuretan dan pengempaan selama 3 jam pada mal pelengkung. Setelah proses pelengkungan dilakukan pengamatan perubahan bentuk pada masing-masing komponen. Penerapan metode bent lamination menghasilkan komponen kaki belakang bentuk lengkung dengan radius 100 mm, 250 mm, dan 290 mm, tebal 40 mm serta lebar 30 mm serta komponen sandaran bentuk lengkung dengan radius 205 mm, tebal 30 mm dan lebar 40 mm. Hasil pengamatan perubahan bentuk tidak ditemukan setelah proses pelengkungan.Kata kunci: bent lamination; furniture, jati, kursi